Similarities and differences in the construction of dispersion laws for charge carriers in semiconductor crystals and adiabatic potentials in molecules - Bercha, S.A.; Rizak, V.M. (Condensed Matter Physics, 2014)
Using the group theory and the method of invariants, it is shown how the vibronic potential can be written in a matrix form and the corresponding adiabatic potentials can be found. The molecule having D₃d symmetry is considered herein as an example. The symmetries of normal vibrations active in Jahn-Teller's effect were defined. E-E vibronic interaction was considered to obtain vibronic potential energy in a matrix form and thus the adiabatic potential. Significant differences are shown in the construction of a secular matrix D(k) for defining a dispersion law for charge carriers in the crystals and the matrix of vibronic potential energy, which depends on the normal coordinates of normal vibrations active in Jahn-Teller's effect. Dispersion law of charge carriers in the vicinity of Γ point of Brillouin zone of the crystal with D₃d² symmetry was considered as an example. У роботi показано як, використовуючи теоретико-груповий метод i метод iнварiантiв, можна одержати
вiбронний потенцiал, записаний у матричному виглядi, та вiдповiднi адiабатичнi потенцiали. В якостi
прикладу розглядається молекула з симетрiєю D₃d
. Визначено симетрiю нормальних коливань, активних в ян-теллерiвському ефектi. Розглянуто E − E вiбронний зв’язок для одержання вiбронної потенцiальної енергiї у матричному виглядi та адiабатичний потенцiал. Вказано на iстотнi вiдмiнностi у побудовi
секулярної матрицi D(~k) для знаходження закону дисперсiї електронного спектру в кристалах i матрицi
вiбронної потенцiальної енергiї, залежної вiд нормальних координат активного в ян-теллерiвському ефектi нормального коливання. В якостi прикладу розглядується закон дисперсiї носiїв струму в околi точки
Γ зони Брiллюена кристалу з симетрiєю D
²
₃d
.